Analytical exploratory tool for healthcare professionals to monitor cancer patients’ progress - Valero-Ramon, Zoe; Fernandez-Llatas, Carlos; Collantes, Gonzalo; Valdivieso, Bernardo; Billis, Antonis; Bamidis, Panagiotis; Traver, Vicente (Frontiers in Oncology, 2023)
Cancer is a primary public concern in the European continent. Due to the large case numbers and survival rates, a significant population is living with cancer needs. Consequently, health professionals must deal with complex treatment decision-making processes. In this context, a large quantity of data is collected during the delivery of cancer care. Once collected, these data are complex for health professionals to access to support clinical decision-making and performance review. There is a need for innovative tools that make clinical data more accessible to support cancer health professionals in these activities. One approach for providing health professionals with access to clinical data is to create the infrastructure and interface for a clinical dashboard to make data accessible in a timely and relevant manner. In this sense, results should be understandable and valuable for cancer experts to evaluate and optimize cancer processes. This work aims to collect and report the process of developing an analytical Interactive Process Mining Dashboard with clinical relevance for healthcare professionals for monitoring cancer patients' care processes in the context of the LifeChamps project. Following a co-creation and interactive approach thanks to the Interactive Process Mining paradigm, the tool presents patients' progress over time for different clinical models as a set of graphical and navigable Process Indicators.